Evolution of Glacial Lake Cochrane During the Last Glacial Termination, Central Chilean Patagonia (∼47°S) - Vásquez, Alicia; Flores-Aqueveque, Valentina; Sagredo, Esteban; Hevia, Rodrigo; Villa-Martínez, Rodrigo; Moreno, Patricio I.; Antinao, Jose L. (Frontiers in Earth Science, 2022)
Large ice-dammed lakes developed along the eastern margin of the Patagonian Ice Sheet (PIS) during the Last Glacial Termination (T1). Their spatial/temporal evolution, however, remains poorly constrained despite their importance for deciphering fluctuations of the shrinking PIS, isostatic adjustments, and climate forcing. Here we examine the distribution and age of shoreline features deposited or sculpted by Glacial Lake Cochrane (GLC) in the Lago Cochrane/Pueyrredón (LCP) basin, Central Patagonia, following recession of the LCP glacier lobe from its final Last Glacial Maximum (LGM) moraines. GLC drained initially toward the Atlantic Ocean and continuing ice shrinking opened new drainage routes allowing the discharge toward the Pacific Ocean. We identify five clusters of lake terraces, shorelines, and deltas between elevations ~600-500 (N5), ~470-400 (N4), ~360-300 (N3), ~230-220 (N2), and ~180-170 masl (N1) throughout the LCP basin. The distribution of these clusters and associated glaciolacustrine deposits provide constraints for the evolving position of the damming glacier bodies. Elevation gradients within the landform clusters reveal glacio-isostatic adjustments that enable us to quantify the magnitude of deglacial rebound and construct isostatically corrected surfaces for the different phases in the evolution of GLC. Our chronology, based principally on radiocarbon dates from lake sediment cores and new OSL dating, suggests that these phases developed between ~20.7-19.3 ka (N5), ~19.3-14.8 ka (N4), ~14.8-11.3 ka (N3), and shortly thereafter (N2 and N1). The N3 landforms are the most ubiquitous, well-preserved, and voluminous, attributes that resulted from a ~3500-yr long period of glacial stability, enhanced sediment supply by peak precipitation regime, and profuse snow and ice melting during the most recent half of T1. This scenario differs from the cold and dry conditions that prevailed during the brief N5 phase and the moderate amount of precipitation during the N4 phase. We interpret the limited development of the N2 and N1 landforms as ephemeral stabilization events following the final and irreversible disappearance of GLC after N3. This event commenced shortly after the onset of an early Holocene westerly minimum at pan-Patagonian scale at ~11.7 ka, contemporaneous with peak atmospheric and oceanic temperatures in the middle and high latitudes of the Southern Hemisphere.